Parent and Medical Professional Willingness to Enroll Children in a Hypothetical Pediatric Optic Neuritis Treatment Trial - Waldman, Amy; Shumski, Michael; Liu, Grant T. (Frontiers in Neurology, 2011)
The Optic Neuritis Treatment Trial and subsequent studies have had a tremendous impact on the treatment and prognosis of optic neuritis and multiple sclerosis in adults. The results of these studies have been extrapolated to children; however, pediatric data are sparse. Using the method of prospective preference assessment, the willingness of parents and medical professionals to enroll children in a hypothetical Pediatric Optic Neuritis Treatment Trial was assessed using a mock consent form and questionnaire. A 3-arm trial was proposed: 1) intravenous corticosteroids, 2) high-dose oral corticosteroids, and 3) an oral placebo. The forms were completed by 198 parents and 49 physicians. After reviewing the hypothetical scenario, trial design, risks and benefits, and alternatives to the study, 21% of parents would enroll their children in the trial whereas 98% of medical professionals would enroll their patients. With medical professional recommendation, 43% of parents would enroll their children. The manner in which this hypothetical trial was presented to parents, specifically with respect to the recommendation of their child’s health care team, influenced a parent’s willingness to participate.